PERTUMBUHAN PENDAPATAN ASLI DAERAH DAN KONTRIBUSINYA TERHADAP BELANJA DAERAH KOTA MANADO - Wendy ., Rawung; Theodora M. Katiandagho; Melissa Lady G. Tarore (Sam Ratulangi University, 2018)
This study aims to find out how much the growth of Regional Original Income (PAD) and the Contribution of PAD to the Regional Expenditures of the City of Manado. This research was conducted for three months from September to November 2017. The data used in this study were secondary data collected from the Central Statistics Agency (BPS) of North Sulawesi. The results showed that the growth of PAD from 2011-2016 was fluctuating with the highest growth rate in 2012 of 24.49% and the lowest in 2015 of 4.22% and with an average of 15.33%. The contribution of Regional Original Revenue to Regional Expenditures for 2011-2016 is still in the lack of criteria, with the highest contribution in 2014 amounting to 19.08% and the lowest in 2016 amounting to 14.91% and the average contribution to Regional Expenditure of 15.75% . This means that the Manado City government needs to improve performance more in exploring new sources of Regional Revenue and maximizing existing PADs to increase Regional Original Income Contributions to Manado City Regional Expenditures.*eprm*.